A Plausible Thermo-Dynamic Cause of an Implausible Psicho-Dynamic Course From The CIA Archive - Piao, Daqing (Journal of Scientific Exploration, 2024)
The STAR GATE archive included an experiment from China of psicho-physical claim reportedly conducted on aqueous object (Wu et al, 1991). Over a time-lapse of approximately 208 seconds, total 7 phases of significant temperature deviation from the baseline temperature of 25 °C may be identified, without an explainable source of thermal generation. Not questioning the genuineness of the experiment, this work analyzes the thermal-energy transfer on the test-object that could have caused the reported temperature changes. A non-adiabatic single-compartment produces first-order low-pass responses between a thermal-input and the object’s temperature. Whereas the input determines the steady-state condition, the thermal dissipation dictates the dynamics. Under the assumption of ONLY first-order responses and adjusting the input parameters including DC and AC magnitudes and time-constant of the single-compartment responses, multi-phase temperature changes resembling the reported patterns could be reconstructed. One rising phase and three falling phases with apparent oscillation were reconstructed by considering the thermal input to contain modulatory patterns of 0.4-0.5 Hz in frequency. Such modeled modulation of the thermal inputs would correspond to a correlation coefficient of 0.95 between the DC and AC magnitudes at a varying AC/DC modulation-depth of 94%. The low-frequency may suggest relevance to altered neuro-electro-physiology.